MODELING OF FACTORS INFLUENCING GENDER DEVELOPMENT INDEX (GDI) IN PAPUA PROVINCE USING SPLINE NONPARAMETRIC REGRESSION - Sintah Sintah; Ferry Kondo Lembang; Norisca Lewaherilla (Jurnal Statistika Universitas Muhammadiyah Semarang, 2024)
The Gender Development Index (GDI) is an index of achieving basic human development capabilities to measure success in efforts to develop the quality of human life by considering gender inequality. Papua Province is the province with the lowest GDI score when compared to the 34 provinces in Indonesia. This condition shows that there is still a development gap between the male and female genders. For this reason, it is necessary to research the factors that are suspected to influence GDI in Papua Province. In this study, the pattern of GDI data and the factors that are thought to influence it do not form a specific pattern, so we used spline nonparametric regression. Based on this study, the best model is obtained by the optimal knot point based on the smallest Generalized Cross Validation (GCV) value, which are 3-knots and six significant variables, namely, Life Expectancy , Expected Years of Schooling , Female Income Contribution , Sex Ratio , Female Labor Force Participation Rate , High School Enrollment Rate. This model has an  of 99.95%. The predictor variable used has an effect of 99.95%, and other variables influence the rest.